(untitled) - Kanoglu, Mehmet (New York, NY, 2020)
Fundamentals and Applications of Renewable Energy helps prepare students for a successful career in renewable energy. The text contains detailed discussions on the thermodynamics, heat transfer, and fluid mechanics aspects of renewable energy systems in addition to technical and economic analyses. Numerous worked-out example problems and over 850 end-of-chapter review questions reinforce main concepts, formulations, design, and analysis.
Keywords: Năng lượng tái sinh,Renewable energy sources